2017
DOI: 10.1177/2051570717716562
|View full text |Cite
|
Sign up to set email alerts
|

Ethical sensitivity: Conceptualization and new scale development

Abstract: This article proposes a new and original measurement scale for consumers’ ethical sensitivity (CES). Usually measured using scenarios, ethical sensitivity appears as a fundamental variable in understanding consumers’ ethical behaviour. In this study, we propose an alternative definition and a new scale for ethical sensitivity. We use a series of qualitative and quantitative studies and analyse construct validity, that is, content, convergent and discriminant validities. The results indicate that ethical sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 83 publications
1
1
0
Order By: Relevance
“…Items are proposed in a 5-option Likert scale and are scored by 1-5, respectively. Toti & Moulins conformed the validity of this scale through EFA and reported the Cronbach's alpha coefficients for the PES and IES as 0.88 and 0.84, respectively (25). Similarly, in the present study, by EFA and CFA, it was found that the scale had a two-factor structure.…”
Section: Ethical Sensitivity Scale (Ess)supporting
confidence: 82%
“…Items are proposed in a 5-option Likert scale and are scored by 1-5, respectively. Toti & Moulins conformed the validity of this scale through EFA and reported the Cronbach's alpha coefficients for the PES and IES as 0.88 and 0.84, respectively (25). Similarly, in the present study, by EFA and CFA, it was found that the scale had a two-factor structure.…”
Section: Ethical Sensitivity Scale (Ess)supporting
confidence: 82%
“…After the evaluation of ethical claims in the advertisement, subjective ambivalence (M = 3.86; SD = 1.46; α = 0.935) and skepticism (M = 4.04; SD = 1.34; α = 0.933) were measured using the same scales as in study 1. We then used the six items to measure PBE (Brunk, 2012) (M = 4.681; SD = 0.86; α = 0.871); ethical sensitivity was measured using four items (Toti and Moulins, 2017) (M = 6.294; SD = 0.80; α = 0.876) and intention to purchase ethical products was measured using three items (Schmidt et al , 2018) (M = 3.5; SD = 1.47; α = 0.946). We measured all scales on a seven-point Likert-type scale (1 = strongly disagree, 7 = strongly agree).…”
Section: Methodsmentioning
confidence: 99%